Effect of gap size and age on climber abundance and diversity in Budongo Forest Reserve, Uganda - Babweteera, Fred; Plumptre, Andrew; Obua, Joseph (African Journal of Ecology, 2000)
A study of the e¡ects of gap size and age on climber abundance and diversity was carried out in Budongo Forest Reserve in Uganda. Data were collected from compartments N5, W21, B1 and B3. Stump records were used to locate and estimate the ages of 78 gaps. Sample plots 5 5m were set up in the gaps to assess climber abundance and diversity. Climbers were more abundant and diverse in gaps that were more than 400m2, 15 months old and had more than 25% canopy opening. Momordica foetida was the most abundant climber species occurring on stems, branches and crowns of seedlings and saplings. There- fore, in order to keep natural regeneration free from climber tangles and produce good quality timber, clim- ber control should be a major activity in tropical high forest management.
Keywords: Abundance; Budongo; Canopy; Climbers; Diversity; Gap